Food security strategy National Food Security Strategy To Improve Economic Independence and Competitiveness In The Framework Of National Resilience: Food Security - Dyah Andrianti; Eva Claudia Boru Lubis; Kiki Nuridayanti; Endar Purnawan (Pascasarjana, Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
Steps to ensure food security in order to increase economic independence and competitiveness while maintaining national resilience are discussed in this article. Based on a literature review analysis, this study highlights Indonesia's agricultural policies and the country's need to control and develop sustainable food security plans due to its favorable position and wealth of natural resources. This study reveals that despite all the wealth that Indonesia has and the supporting factors that exist, it is not enough to become a strength in national food security. Therefore, to ensure national food security, unique planning and strategies are needed that support independence and healthy competition. Research findings show that sustainable food systems from upstream to downstream can be used to strategically achieve sustainable food security and increase national food supplies. Food independence is then achieved through achieving food diversity, which leads to achieving food security. Overall, the findings of this study underline the importance of supporting industries such as banks, universities, agricultural extension centers as supporting industries in the implementation and success of the national food security strategy.